LINC00242/miR-1-3p/G6PD axis regulates Warburg effect and affects gastric cancer proliferation and apoptosis - Peng Deng; Kai Li; Feng Gu; Tao Zhang; Wenyan Zhao; Ming Sun; Bin Hou (BMC, 2021)
Abstract Background Reprogrammed glucose metabolism of enhanced Warburg effect (or aerobic glycolysis) is considered as a hallmark of cancer. Long non-coding RNAs (lncRNAs) have been certified to play a crucial role in tumor progression. The current study aims to inquire into the potential regulatory mechanism of long intergenic non-protein coding RNA 242 (LINC00242) on aerobic glycolysis in gastric cancer. Method LINC00242, miR-1-3p and G6PD expression levels in gastric cancer tissues and cells were determined by qRT-PCR. Cell apoptosis or viability were examined by Flow cytometry or MTT assay. Western blot was utilized to investigate G6PD protein expression levels. Immunohistochemical (IHC) and hematoxylin and eosin (H&E) staining were used for histopathological detection. The targeted relationship between LINC00242 or G6PD and miR-1-3p was verified by luciferase reporter gene assay. Nude mouse xenograft was utilized to detect tumor formation in vivo. Result LINC00242 and G6PD was high-expressed in gastric cancer tissues and cells, and LINC00242 is positively correlated with G6PD. Silencing of LINC00242 or G6PD within gastric cancer cells prominently inhibited cell proliferation and aerobic glycolysis in vitro and relieved the tumorigenesis of gastric cancer in vivo. miR-1-3p was predicted to directly target both LINC00242 and G6PD. Overexpression of miR-1-3p suppressed gastric cancer cells proliferation and aerobic glycolysis. LINC00242 competitively combined miR-1-3p, therefore relieving miR-1-3p-mediated suppression on G6PD. Conclusion LINC00242 plays a stimulative role in gastric cancer aerobic glycolysis via regulation of miR-1-3p/ G6PD axis, therefore affecting gastric cancer cell proliferation.